Pengaruh Citra merek dan Kualitas Produk terhadap Harga dengan Minat Beli Konsumen sebagai Variabel Intervening ( Studi Kasus Pengguna Aplikasi Shopee di Kota Solok) - Rizalina; Nadirman (CV. ITTC INDONESIA, 2022)
This research aims to analyze the influence of brand image, product quality, on consumer buying interest in Shopee application users. This research was conducted on Shopee Application users and determined consumers' buying interest in online shopping using the Shopee Application in Solok City. The sample was determined using a purposive sampling method with a total of 80 respondents aged 18-40 years. The results of this research show that brand image, product quality, both partially and simultaneously have a positive and significant effect on purchase intention. The variables brand image, product quality, were able to explain the purchase interest variable by 87% and the remaining 13% was explained by other variables not included in the research